Daring to challenge OCD : overcome your fear of treatment and take control of your life using exposure & response prevention - Davidson, Joan, 1960- (Oakland, CA : New Harbinger Publications, Ltd., 2014)
"If you have obsessive-compulsive disorder (OCD), you may suffer from obsessive thoughts and anxiety, and use compulsions to alleviate your distress. You know, more than anyone, how debilitating this condition can be. But you may also be reluctant to start treatment due to fears and misconceptions regarding therapy-particularly exposure and response prevention (ERP) therapy. You may even think of a number of reasons not to go, or to drop out, but if you are committed to getting better, you need to take that important step toward healing. ERP is a proven-effective treatment that can help people with OCD break free from the constraints of their disorder; however, starting treatment can feel frightening. Many people wonder what treatment will be like and how they will ever face some of their worst fears. They want to hear from others who have successfully completed therapy. In Daring to Challenge OCD, anxiety specialist Joan Davidson, PhD, gives a thorough overview of ERP, what to expect during treatment, and offers gentle guidance to help you finally overcome the common fears and obstacles that can stand in the way of getting the help you need. Three clients with different OCD symptoms share their personal stories and insights about OCD and treatment. If you are considering treatment, you may ask yourself, What will my therapist expect me to do? Will treatment be too difficult for me to handle? Will I be asked to do things that put me at risk? What are realistic expectations for recovery? This book will demystify treatment for OCD so that you can face your fears and start changing your life. And if you are a therapist helping clients build motivation to engage in ERP, this book offers real treatment stories and exercises for clients, making it an invaluable resource for therapists and wonderful suggested reading for clients building motivation to commit to treatment"--
"Characterized by obsessive thoughts, anxiety and compulsions, obsessive-compulsive disorder (OCD) can be an extremely debilitating condition. However, many people with OCD are reluctant to start treatment due to fear, stigma, and misconceptions regarding exposure and response prevention (ERP) therapy. In Daring to Challenge OCD, anxiety specialist Joan Davidson, PhD, gives a thorough overview of ERP, what to expect during treatment, and offers guidance to help readers finally overcome the common fears and anxiety that can stand in the way of getting the help they need"--
Machine generated contents note: 1.Understanding OCD -- 2.The OCD Cycle -- 3.Getting the Help You Need -- 4.Why Treatment Is Worth It -- 5.Getting Started with Exposure and Response Prevention -- 6.Putting Exposure and Response Prevention into Action -- 7.Overcoming Obstacles -- 8.Realistic Expectations for Recovery.
Includes bibliographical references (pages 181-184)
Keywords: Obsessive-compulsive disorder -- Treatment; Exposure therapy